Determinants of relationship quality : a cross-cultural study - Tadinac, Meri (Array, 2012)
It has been suggested that the cross-cultural universality of pair-bonding reflects its adaptive function. Along with this line of reasoning, we hypothesised that partners’ perceptions of the relationship quality should also be determined by a cross-culturally universal mechanism of cost- benefit analysis. Therefore, the aim of this study was to compare the predictors of relationship quality in two different cultures and explore which features of a relationship might be considered as universal predictors of its quality. Ninety-nine Iranian married and 99 Croatian married or cohabiting couples were included in a dyadic assessment. The highest between-culture similarities were found for the “frequency of positive interactions” and the “profit in mate value” (difference in own and partner’s perceived mate value). Sexual satisfaction proved to be a significant predictor only in the Croatian sample, while the number of children predicted the relationship quality in Iranian couples only. Other variables, such as difference in partners’ age, income and education showed a more complex culture-and gender-dependent pattern. The results are in accordance with the notion that while the cost-benefit analysis itself is a universal process, the perception of certain costs and benefits is culturally specific.